Changes of clinical parameters at implants: a retrospective comparison of implants versus natural teeth over 5 years of supportive periodontal therapy - Sonnenschein, Sarah K.; Kohnen, Rebecca; Ciardo, Antonio; Ziegler, Philipp; Seide, Svenja; Kim, Ti-Sun (Clinical oral implants research, 2020)
Objectives To compare clinical parameters of implants versus natural teeth over a period of 5 years during supportive periodontal therapy (SPT). Material and Methods A total of 421 SPT patients were screened for implants (I) and corresponding control teeth (C). Data (patient level [P]: sex, age, smoking status, systemic diseases, adherence, oral hygiene indices, mean probing depth [PD]P, bleeding on probing [BOP]P, periodontal risk profile; implant/control tooth level [I/C]: PDI/C, BOPI/C; site level at implants [SITE]: position, dental arch, aspect, BOPSITE) were assessed at the first SPT session where the implant was probed (T1) and 5 years later (T2). The influence of patient and implant/control-related factors on PDI/C/BOPI/C was tested (linear mixed model) as well as the influence of site-specific factors on the PDSITE change (multilevel regression). Results A total of 70 patients (151 implants) were included. Mean PDI was 2.75 ± 0.85 mm (T1) and 2.87 ± 0.79 mm (T2). Mean PDC was 2.42 ± 0.66 mm (T1) and 2.49 ± 0.71 mm (T2). BOPI increased from 8.62 ± 15.01% (T1) to 24.06 ± 26.79% (T2) and BOPC from 9.97 ± 17.78% (T1) to 15.52 ± 22.69% (T2). The differences between implants and controls were significant for BOP (p = .0032). At T2, BOPI/C was associated with periodontal risk (p = .0351). The site-specific analysis revealed an association of BOPSITE at T1 with the progression of PDSITE (p = .0058). Conclusions Probing depths of implants and controls seem to change similarly during SPT but retention of inflammation-free conditions at implants appears to be more difficult compared to natural teeth. Patients with a high-risk profile appear to have an increased susceptibility for BOP around implants, and BOP at implants seems to be a predictor for further PD increase.
Gesehen am 12.08.2021